Lovers Versus Haters Contestation In Cyberbullying Behavior On Social Media Platform Instagram - Nur Maulidin; Moch Alan Firmansyah; Erlangga Dwi Andika; Khaerudin Imawan; Dedet Erawati (Asian Journal of Social and Humanities, 2024)
In the 20th century the digital era began to develop and when computer technology slowly began to enter various industries which then moved into the public domain, from the massive development of digitalization flows that always experienced a significant increase in users in all parts of the world, including in Indonesia in the use of digital channels so that eventually it became a digital communication. One of the digital channels that people need in everyday life is a social media platform where people use it to exchange information effectively and efficiently. Cyberbullying behavior or cases in Indonesia always increase every year because many of Instagram's social media users get cyberbullying treatment and a public figure is no exception. This study will look at the contestation of likes and dislikes from netizens or in this case lovers and haters that occur on Instagram social media, using the reciprocal determination model from Albert Bandura's social cognitive theory Researchers will see and observe how cyberbullying on Instagram social media continues to exist and seems to never end. Researchers will use a qualitative method approach used by researchers to study the state of an object and rely on a narrative approach from facts found during field observations, while the type of data used is more likely to be primary data obtained from literature tracing such as books, scientific journals, and news and observations that occur in existing phenomena and are related to research problems.